Explicit enriched plate model for laminated glass - Claude Boutin (Challenging Glass Conference, 2018)
This abstract relates to the recent publication [Viverge K., Boutin C., Sallet F. : Model of highly contrasted plates versus experiments on laminated glass, IJSS, 102-103, 238-258 (2016)]. This contribution provides a synthetic analytic formulation describing the behaviour of laminated glass under static and dynamic loadings, that is validated by experiments. We only give here a synoptic overview and for in depth reading one may refer to the above mentioned publication.